Determinants of Credit Spreads on Asset-Backed Securities: A British Case Study in the Context of the COVID-19 Pandemic - Shen, Jiaqi (2021)
The determinants of credit spreads on asset-backed securities are an active topic of discussion in the literature. This study is aimed to close the gap in research regarding the impact of the COVID pandemic on the determinants of credit spreads of the asset-backed securities in the United Kingdom. The pandemic, as a crucial event, is a key factor influencing the economy. Furthermore, other relevant factors for tranches are considered in the analysing as well. This paper focuses on asset-backed securities excluding MBS. The sample of this study was collected from 201 asset-backed securities and their tranches issued from January 2010 to July 2021 and traded in the United Kingdom (in British pounds). The collected data were analysed by the ordinary least squares (OLS) method in the multiple cross-sectional models. This study explores the factors that impact credit spreads in the context of the COVID-19 pandemic and encourages financial market participants to make appropriate investment strategies on asset-backed securities. This paper provides two main contributions to the literature. First, the credit spreads of non-prime tranches have more positive changes than prime ones during COVID. Second, the link between the maturity of consumer tranches and credit spreads shifts from negative to positive after the COVID break-out. This means that if investors are risk-averse, they should invest in short-term asset-backed securities to reduce credit risk during COVID. This study is modest to fill the literature gap with the COVID-19 factor in analysing the determinants of credit spreads on asset-backed securities. The study also adds to a better understanding of the behaviour of investing in asset-backed securities, both from the perspective of investors and academics. Keywords: Asset-backed Securities (ABS); COVID-19; Ordinary Least Squares (OLS)